Effects of variation of centres on the torsional analysis of asymmetrical buildings - Siddiqui, Muhammed Masihuddin; Krishna, N. Murali (Journal of Structural Engineering, 2024)
Presence of torsion makes the structural design of irregular buildings more complex and is prone to more severedamage. According to IS-1893:2016, a building is said to be torsionally irregular when the ratio of maximum horizontaldisplacement at any floor in the direction of lateral force to the minimum horizontal displacement at far end is morethan 1.5. The torsional forces acting on a building are influenced by the relative location of the centre of mass, thecentre of strength and the centre of stiffness. Therefore, these centres of significance shall be located aptly to minimisetorsional effects on buildings to ensure efficient building structure. In this paper, the effects of strength eccentricity andstiffness eccentricity with respect to the centre of mass of the building are evaluated and non-linear dynamic analysisis carried-out to study the variation on torsional irregularity ratio and other torsional parameters. For the buildingstructure, the structural configuration together with the sizes of structural elements are varied repeatedly to find-outthe best locations of mass, stiffness and strength centres to minimize the torsional irregularity ratio. The study is foundto be very productive as the torsional irregularity ratio gets reduced very significantly.